A fuzzy-based PI controller for power management of a grid-connected PV-SOFC hybrid system - Sukumar S.; Marsadek M.; Ramasamy A.; Mokhlis H.; Mekhilef S. (MDPI AG, 2023)
Computer circuits; Controllers; Distributed power generation; Electric power transmission networks; Fuel cells; Fuzzy logic; Genetic algorithms; Hybrid systems; Linear programming; Power control; Power management; Solar energy; Solar power generation; Solar radiation; Solid oxide fuel cells (SOFC); Control parameters; Fuzzy logic controllers; Maximum power point; Photovoltaic; Photovoltaic systems; Power management systems; Proportional and integral controllers; Sofc hybrid systems; Electric power system control